Hypertension in Childhood Nephrotic Syndrome - Shatat, Ibrahim F.; Becton, Lauren J.; Woroniecki, Robert P. (Frontiers in Pediatrics, 2019)
Arterial hypertension (HTN) is commonly encountered by clinicians treating children with steroid sensitive (SSNS) and steroid resistant nephrotic syndrome (SRNS). Although the prevalence of HTN in SSNS is less documented than in SRNS, recent studies reported high incidence in both. Studies have estimated the prevalence of HTN in different patient populations with NS to range from 8% to 59.1%. Ambulatory HTN, abnormalities in BP circadian rhythm, and measures of BP variability are prevalent in patients with NS. Multiple mechanisms and co-morbidities contribute to the pathophysiology of HTN in children with NS. Some contributing factors are known to cause acute and episodic elevations in blood pressure such as fluid shifts, sodium retention, and medication side effects (steroids, CNIs). Others are associated with chronic and more sustained HTN such as renal fibrosis, decreased GFR, and progression of chronic kidney disease. Children with NS are more likely to suffer from other cardiovascular disease risk factors such as obesity, increased measures of arterial stiffness (increased carotid intima-media thickness (cIMT), endothelial dysfunction, increased pulse wave velocity (PWV)), impaired glucose metabolism, dyslipidemia, left ventricular hypertrophy, left ventricular dysfunction, and atherosclerosis. Those risk factors have been associated with premature death in adults. In this review on HTN in patients with NS, we will discuss the current HTN definition, epidemiology and pathophysiology of hypertension in patients with NS, as well as management aspects of HTN in children with NS.